Design and Validation of an Emotional Intelligence Educational Package Based on Bar-On Theory Using Psychodrama for Adolescent Girls - Hosseini , Seyede Masoome; Nejat, Hamid; Akbari, Ahmad; Saffarian Toosi, Mohammadreza (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective:  The purpose of this study was to design and validate an emotional intelligence educational package based on Bar-On’s theory and implemented through psychodrama techniques for adolescent girls in foster care centers.Methods and Materials: This applied developmental study was conducted in three stages. First, a twelve-session educational package was designed using Bar-On’s emotional intelligence model as the theoretical framework and psychodrama as the methodological basis. Second, content validity was assessed by five experts using the Content Validity Ratio (CVR) and Content Validity Index (CVI). Third, the package was piloted with five adolescents from foster care centers in Mashhad in 2024, followed by refinement and final implementation with fifteen adolescents residing in welfare residential homes. Data collection involved expert evaluations, facilitator observations, and participant feedback, while data analysis used both quantitative validation indices and qualitative thematic review of pilot outcomes.Findings: Content validity indices indicated strong relevance and necessity for all package components (CVR = 1.00; CVI > 0.79). Expert consensus confirmed alignment of the sessions with Bar-On’s theoretical dimensions of intrapersonal skills, interpersonal skills, adaptability, stress management, and general mood. Pilot results suggested improvements in adolescents’ self-awareness, assertiveness, and independence.Conclusion: The integration of Bar-On’s emotional intelligence model with psychodrama techniques resulted in a validated, practical, and replicable training package. The program demonstrated effectiveness in improving core emotional and social skills, making it a promising intervention for adolescents in foster care settings. Its structured format, cultural adaptability, and experiential methodology highlight its potential for application in educational and clinical contexts.